Congruence of Personal and Organizational Values - Vveinhardt, Jolita (IntechOpen, 2017)
Perceived importance of personal and organizational values congruence in the management of organizations have actualized this phenomenon in both theory and practice. Researchers continuously show positive impact of personal and organizational values congruence on employees? behavior, attitudes, organizational climate and organizational performance. Management of organizations are also seeking to apply the solutions to eliminate the gap between organizational and employees' values. However, arising scientific and practical problems requires to purify the factors that determine values congruence. This challenges for a search of complex and consistent understanding of this phenomenon: from theory to practice. This book aims to provide the reader with a comprehensive overview of the personal and organizational values congruence phenomenon, featuring the most important critical issues regarding the exposure, diagnosis and strengthening of congruence of personal and organizational values.